EFFECTIVENESS OF WASH METHOD ON MENSTRUAL HEALTH AMONG ADOLESCENT GIRLS AT SELECTED SCHOOL, CHENNAI - Florence Nightingale K A,; Dr. Savithri K B,; Shevani B,; Muthu Selvan N V,; Nancy. J,; Nadana S,; Nandhini S,; Nikitha. V,; Mythri.T.N, (The Bioscan, 2026)
Background Menstrual health management remains a major concern for adolescent girls, particularly in low-resource school environments where water, sanitation, and hygiene (WASH) facilities are inadequate. Poor knowledge and lack of proper hygiene practices during menstruation negatively affect girls’ school attendance, participation, and overall well-being. Structured educational interventions and improved WASH accessibility can significantly enhance menstrual health knowledge and reduce related stigma. Aim of the Study: The atudy aimed to assess the effectiveness of a structured WASH-based information booklet on improving menstrual health knowledge among adolescent girls. Methods: A quantitative one-group pre-test and post-test research design was adopted among 100 adolescent girls aged 12–18 years who had attained menarche at a selected school. A structured questionnaire assessed demographic variables and menstrual health knowledge. After the pre-test, an information booklet on WASH practices was administered, followed by a post-test. Data were analyzed using descriptive and inferential statistics, including paired t-test and chi-square test.Results: Before the intervention, 58% of the participants demonstrated poor menstrual health knowledge, while none achieved an extremely effective level. Following the WASH intervention, 59% reached an extremely effective knowledge level and no student remained in the poorly effective category. The mean score increased from 10.74 in the pre-test to 21.02 in the post-test, showing a highly significant improvement (p < 0.001). Educational standard and age at menarche showed significant association with post-test knowledge levels. Conclusion: The WASH intervention significantly improved menstrual health knowledge among adolescent girls. Culturally appropriate WASH-based education programs in schools can enhance menstrual health practices and support improved academic participation and well-being. Keywords Menstrual health, WASH intervention, adolescent girls, school hygiene, knowledge improvement